Elderly Exercises and Finger Grip Relaxation to Reduced Blood Pressure - Indra Ruswadi; Masliha (Jurnal Penelitian Pendidikan IPA, 2024)
The elderly experience a phase of decline in all body organ functions, such as social, physical, psychological and emotional abilities which become increasingly weakened so that the elderly become vulnerable. fights various diseases, including hypertension. Elderly exercise and finger grip relaxation are non-pharmaceutical therapies that are believed to lower blood pressure. This study aims to determine the effect of elderly exercise and finger grip relaxation on reducing blood pressure. The research design used was a quasi-experimental nonequivalent control group pre-post test design. The research sample consisted of 114 respondents who were divided into 3 groups of 38 respondents each, with inclusion criteria: Elderly people suffering from hypertension, minimum age 60 years, currently taking antihypertensive medication, blood pressure >140/90 mmHg, able to participate in gymnastics movements. / can move the whole body, does not smoke and is not obese. Group selection used consecutive sampling techniques. The research location was carried out in the Cantigi Community Health Center working area and the Wilcoxon and Mann Whitney tests were used to analyze this research data. Research results: systolic and diastolic blood pressure before and after the test in the control group (systolic p = 0.480 and diastolic p = 0.301), systolic and diastolic blood pressure before and after the test in the exercise group (systolic p and diastolic p = 0.001), as well as relaxation of finger grip on a decrease in blood pressure (systolic p = 0.001 and p = 0.012 diastolic). The difference in systolic and diastolic blood pressure after elderly exercise and finger grip relaxation shows that elderly exercise produces lower diastolic blood pressure results compared to finger grip relaxation (diastolic p = 0.015 and 0.005). Conclusion: elderly exercise and finger grip relaxation have an effect on reducing blood pressure and elderly exercise produces lower diastolic blood pressure results compared to finger grip relaxation (diastolic p = 0.015 and 0.005).